الأزمة المالية العالمية 2008 وآثارها على التنمية الدولية (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف هذا البحث إلى تسليط الضوء على الأزمة المالية العالمية ومدى تأثيرها على التنمية الدولية, وتطرق إلى أنواع الأزمات والمؤشرات الاقتصادية المرافقة لتلك الأزمات, و شخص البحث الأزمة المالية العالمية في عام 2008, ومراحلها وكيفية حدوثها, ثم تطرق إلى البحث في أسبابها ومظاهرها وأهم القطاعات التي تضررت من تلك الأزمة, و أهم أضرارها على التنمية الدولية. وبين البحث آثار الأزمة المالية على الأسواق المالية و التنمية الدولية وخطط معالجتها سواءً في الولايات المتحدة الأمريكية أو الدول الصناعية أو البلدان النامية واستجابة الدول والمنظمات لها. وتوصل البحث إلى العديد من النتائج, وقدم بعض المقترحات. This research aims to shed light on the global financial crisis and its impact on international development, and touched on the types of crises and economic indicators associated with these crises, and people search the global financial crisis in 2008, and the stages and how they occur, then turned to look at the causes and manifestations and the most important sectors those affected by the crisis, and the most harmful to the international development. The research explained the effects of the financial crisis on the financial markets and international development plans and addressed both in the United States or the industrialized nations or the developing countries , and Responding of the countries and organizations to it .The research found a number of results, and made some proposals.